The physics of the standard model and beyond - Morii, T (World Scientific, 2004)
Includes bibliographical references (pages 291-294) and index.; This book provides a unified description of elementary particle interactions and the underlying theories, namely the Standard Model and beyond. The authors have aimed at a concise presentation but have taken care that all the basic concepts are clearly described. Written primarily for graduate students in theoretical and experimental particle physics, The Physics of the Standard Model and Beyond conveys the excitement of particle physics, centering upon experimental observations (new and old) and a variety of ideas for their interpretation.